Digitalization of Islamic Education Based on Muhammadiyah Da'wah: Building Tolerance and Religious Literacy in the Society 5.0 Era - Syarifan Nurjan; Fifi Arisanti; Jawwad Sulthon Habiby; Asis Riat Winanto (Al-Qalam Institute, 2025)
The digitalization of Islamic education based on Muhammadiyah da'wah has become an innovative strategy to enhance religious literacy and tolerance in the Society 5.0 era. This study aims to analyze the role of digitalized Muhammadiyah da'wah in fostering a moderate and inclusive understanding of Islam. The research employs a descriptive qualitative method with data triangulation through interviews, observations, and document analysis. The findings indicate that digital da'wah utilizing social media and digital platforms can expand the reach of Islamic literacy and increase awareness of religious tolerance in society. This strategy effectively addresses the challenges of conventional da'wah while fostering active engagement among younger generations in understanding Islam as rahmatan lil ‘alamin. The implications of this study suggest that the development of Muhammadiyah's digital da'wah holds significant potential for transforming Islamic education into an inclusive, collaborative, and technology-driven system. Therefore, optimizing the use of digital media should be continuously developed to support broader and more sustainable religious literacy.